Assessing Critical Success Factors for PPP Water Project in Indonesia: Lessons from West Semarang - Nabila Puspa Adiyanti; Reza Fathurrahman (Policy & Governance Review, 2021)
A very low success rate of PPP infrastructure projects between 2005 and 2015 has encouraged the Indonesian government to adopt the BOT scheme as the main strategy to accelerate the progress. Although the National Government has attempted to amend the presidential regulations three times in a row, only one out of seven priority national water supply projects reached a financial close and started the project. Using Ameyaw and Chan’s theoretical framework (2016), this article examines the case of West Semarang as a leading example to improve understanding of the key success factors for successful PPP implementation in Indonesia’s drinking water supply sector. Multi- perspective data, incorporating views of national and local actors and relevant government documents, were analyzed for the purpose of this study. The findings highlight five critical success factors: Strong commitment from the contracting agency, as well as local and national government, experienced project partners, long-term capital, tangible political support, and the existence of Indonesia PPP Joint Office. Finally, recommendations to improve PPP implementation in drinking-water projects are suggested accordingly.